A study on Macau’s role in the eastward spread of western medicine from the perspective of procedural grounded theory - Wu, Baoling; Gong, Hanxiang; Wang, Xi (Medicina Historica, 2024)
Objective: This study aims to elucidate the origins of the eastward spread of Western medicine, trace its dissemination in China, and examine Macau’s role in this process. The objective is to verify the profound impact of the Western medical knowledge system on the healthcare system in Macau. Method: Research samples were extracted from ten classic medical history writings discussing the eastward spread of Western medicine or related to Western medicine in Macau. Based on procedural grounded theory, open coding, axial coding, and selective coding were performed using Nvivo. Results: A total of 798 coding references were generated, forming 39 concepts, six subcategories, and two categories, with “medical treatment” as the core category to construct a framework for analyzing Macau’s role in the spread of Western medicine. Conclusion: Macau served as the initial entry point for Western physicians into China, facilitating the introduction of a significant number of Western drugs and medical techniques. Western medical missionaries established hospitals in Macau and extended their influence to mainland China. They also played a crucial role in disseminating Western medical knowledge by translating and compiling Western medical literature.